Effective Biotransformation of Variety of Guaiacyl Lignin Monomers Into Vanillin by Bacillus pumilus - Zuo, Kangjia; Li, Huanan; Chen, Jianhui; Ran, Qiuping; Huang, Mengtian; Cui, Xinxin; He, Lili; Liu, Jiashu; Jiang, Zhengbing (Frontiers in Microbiology, 2022)
Biotransformation has gained increased attention due to its being an eco-friendly way for the production of value-added chemicals. The present study aimed to exploit the potential of Bacillus pumilus ZB1 on guaiacyl lignin monomers biotransformation for vanillin production. Consequently, isoeugenol, eugenol, and vanillyl alcohol could be transformed into vanillin by B. pumilus ZB1. Combined with the structural alteration of masson pine and the increase of total phenol in the supernatant, B. pumilus ZB1 exhibited potential in lignin depolymerization using masson pine as the substrate. As the precursors of vanillin, 61.1% of isoeugenol and eugenol in pyrolyzed bio-oil derived from masson pine could be transformed into vanillin by B. pumilus ZB1. Four monooxygenases with high specific activity were identified that have been involved in the transformation process. Thus, B. pumilus ZB1 could emerge as a candidate in the biosynthesis of vanillin by using wide guaiacyl precursors as the substrates.